2012
DOI: 10.4236/am.2012.330214
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Backtrack Optimization Technique to Obtain Forecasts of Potential Crisis Periods

Abstract: Financial crisis is an unfortunate reality that overshadows any financial system regardless its profitability and the level it functions. The appearance of crises across financial markets, especially during the 1990s that the internationalized markets adopted a rather approachable character, imposed severe costs in financial and social systems. With this paper is proposed the generation of a future interval of time that is vulnerable to enclose the burst of a financial crisis. A time series consisted of approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Backtrack [14] is an optimum seeking method which searches forward according to the selection conditions to achieve a goal. If at a certain step of the search, it is found that the goal turns out to be unachievable, then a step backward is taken.…”
Section: Related Workmentioning
confidence: 99%
“…Backtrack [14] is an optimum seeking method which searches forward according to the selection conditions to achieve a goal. If at a certain step of the search, it is found that the goal turns out to be unachievable, then a step backward is taken.…”
Section: Related Workmentioning
confidence: 99%
“…A CSP is generally solved by search strategies, among which backtracking algorithms [27] are widely used. In this paper, the process of exploring the solution space is represented by state space search [28] in artificial intelligence.…”
Section: Figure 1 Program Test1 and Its Corresponding Cfgmentioning
confidence: 99%